Prehistoric fisherfolk of Oman : the Neolithic village of Ras Al-Hamra RH-5 - Marcucci, Lapo Gianni, (Archaeological heritage of Oman., 2021)
Here are reports on excavations at the prehistoric site Ras Al-Hamra RH-5, located in the Qurum area of Muscat. The site dates from the late 5th to the end of the 4th millennia BC and comprises an accumulation of superimposed food discards deriving from continuous and repeated subsistence activities such as fishing, collecting shells, hunting, and herding.